Preparation of ammonia feedstock through high-temperature co-electrolysis of air and water - Chan, Natalie En Lin (2018)
Being one of the most important chemicals, ammonia is produced in massive quantities for use in many industries. The conventional ammonia synthesis process has a significant negative impact on the environment. Therefore, considering the global climate change and the depletion of fossil fuels, it is crucial to develop a sustainable method of ammonia synthesis with minimised, or even zero carbon emissions. This project aims to develop a renewable ammonia synthesis method by integrating high temperature electrolysis cell into the conventional Haber Bosch process for ammonia synthesis. In this project, preliminary experiments have been conducted to produce a mixture of hydrogen and nitrogen as ammonia feedstock through the co-electrolysis of wet air using high temperature electrolysis cell with LSCM-GDC fuel electrode. The electrochemical behaviour of the fuel electrode have been examined under various conditions involving water electrolysis, air electrolysis as well as co-electrolysis of wet air. Gas chromatography (GC) was used to analyse the composition of the exit gas from the electrode chamber when the cell is operated under constant current. So far, no similar research activity has been reported in the open literature. The GC results have revealed that oxygen electrolysis takes place first under low cell voltages, while high cell voltage is needed to initiate the water electrolysis. The electrochemical results showed that for the co-electrolysis of wet air, the flow rate of air has no effect on the cell performance at voltages below 0.4V. When the air flow rate is smaller than 20 sccm, the I-V curves exhibit limiting current behaviour in the voltage range of 0.4V to 1.1V where the oxygen electrolysis is dominant. However, as water electrolysis starts to occur at voltages higher than 1.1V, current density increases further from the limiting current. It is also found that when the steam concentration in the wet air is increased, current density decreases at lower cell voltages where oxygen electrolysis is dominant. At the voltages above 1.1V, the difference between current densities for different gas compositions decreases as water electrolysis starts to take place. The current densities for different steam concentration eventually become very similar when the voltage increases to 1.5V, as a result of combined contribution of oxygen electrolysis and water electrolysis. When wet air co-electrolysis is conducted at 900°C, with 70% H2/ 30% air at 5 sccm air flow rate, oxygen in the feedstock is totally exhausted and hydrogen gas is detected at a co-electrolysis current of 0.6A. The H2:N2 ratio achieved is 1:2.8, which is far from the desired ratio of 3:1 required for ammonia synthesis. Therefore, to achieve the required ratio, the electrode performance has to be significantly enhanced. However, considering that a half-cell with thick electrolyte substrate is used in the current experiment, a higher H2:N2 ratio can be expected from a full-cell with thin film electrolyte.